FAKTOR-FAKTOR YANG MEMPENGARUHI PENGAMBILAN KEPUTUSAN WISATAWAN DOMESTIK UNTUK BERBELANJA DI PUSAT OLEH-OLEH ERLANGGA 2, DENPASAR – BALI - Anggriawan, Yosia Nanda; Dewi, Luh Gede Leli Kusuma; Suardana, I Wayan (Jurnal Analisis Pariwisata, 2021)
This research purpose to find out the factors affecting domestic tourist decision. The data collected in this research was the observation, in-depth interviews, distributing questionnaires, literature study and documentation. The method used is descriptive qualitative data and quantitative data, data sources are primary data and secondary data. Mechanical determination of informants using purposive sampling and random sampling, with a sample size of 100 respondents tourists, while the data analysis technique using the factor anylisis such as validity and reliability test, bartlet test, KMO, MSA, interpretation factor and rotated factor. Based on the results of a research, factors that influence domestic tourists to shop in Erlangga 2 there are 4 (four) factors that are spiritual factor, social factor, psychological factor and external factor. Of the four factors that are most dominant in giving influence in influencing the domestic tourists to shop in Erlangga 2 is a situational factor with the indicator consist of shopping time, product usage and physical condition when shopping. Keywords : making decision, domestic tourists, shopping. tourism